An Evaluation of Phenolic Compounds, Carotenoids, and Antioxidant Properties in Leaves of South African Cultivars, Peruvian 199062.1 and USA's Beauregard - Phahlane, Charmaine J.; Laurie, Sunette M.; Shoko, Tinotenda; Manhivi, Vimbainashe E.; Sivakumar, Dharini (Frontiers in Nutrition, 2021)
In this study, leaves of sweet potato cultivars from South Africa (“Ndou,” “Bophelo,” “Monate,” and “Blesbok”), “Beauregard,” a sweet potato cultivar from the USA, and a Peruvian cultivar “199062. 1” were analyzed using UPLC/QTOF/MS and chemometrics, with the aim of characterizing the locally developed sweet potato cultivars and comparing them with already well-known established varieties on the market. A set of 13 phenolic compounds was identified. A partial least squares discriminant analysis, a hierarchical cluster analysis, and variables importance in projection were used to successfully distinguish sweet potato varieties based on their distinct metabolites. Caffeic acid enabled to distinguish Cluster 1 leaves of varieties (“Beauregard” and “Ndou”) from Cluster 2 (“199062.1,” “Bophelo,” “Monate,” and “Blesbok”). The leaves of “Bophelo” contained the highest concentrations of rutin, quercetin 3-O-galactoside, 3-caffeoylquinic acid (3-CQA), (5-CQA), 1,3 dicaffeoylquinic acid (1,3-diCQA), 1,4-diCQA, and 3,5-diCQA. Furthermore, Bophelo leaves showed the highest antioxidant activities (FRAP 19.69 mM TEACg−1 and IC50 values of (3.51 and 3.43 mg ml−1) for DPPH and ABTS, respectively, compared to the other varieties. Leaves of “Blesbok” contained the highest levels of β-carotene (10.27 mg kg−1) and zeaxanthin (5.02 mg kg−1) on a dry weight basis compared to all other varieties. This study demonstrated that the leaves of local cultivars “Bophelo” and “Blesbok” have the potential to become functional ingredients for food processing.